2013
DOI: 10.1002/pen.23762
|View full text |Cite
|
Sign up to set email alerts
|

Continuously extruded micro‐textured polypropylene films

Abstract: The continuous extrusion of micro-textured isotactic polypropylene (i-PP) film and its tribological properties are reported. As analyzed by scanning electron microscopy, a rectangular-semicircular micro-patterned die successfully produced extruded cast-films with hill-like micro-texture. Such films displayed static and kinetic coefficients of friction (COF s and COF k ) values of 0.247 6 0.028 and 0.245 6 0.003, respectively, for a steel fixture sliding along the micro-texture of the film. The equivalent COF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…All these methods are batch processes that are too slow and expensive for large-scale production of textured films. In an earlier study [ 33 ], we have successfully demonstrated the processing of neat (unfilled) polypropylene into textured films.…”
Section: Introductionmentioning
confidence: 99%
“…All these methods are batch processes that are too slow and expensive for large-scale production of textured films. In an earlier study [ 33 ], we have successfully demonstrated the processing of neat (unfilled) polypropylene into textured films.…”
Section: Introductionmentioning
confidence: 99%